THE (NON)EXISTENCE OF EQUAL OPPORTUNITY AND ROMANIAN FEMINISM AT THE END OF THE 19TH CENTURY AND THE BEGINING OF THE 20TH CENTURY - Valentina Tănase (Romanian Journal of Historical Studies, 2018)
This study aims to analyse the issue of women’s status in Romanian society from the perspective of legal nature regulations that will eventually emphasize the social framework at the end of the 19th Century and the beginning of the 20th Century, in which Romanian feminism is manifested. At the end of the 19th Century, as the feminist movement begins to manifests here, the purpose of feminists’ actions was to contest the inferior position of women not only at the legal level but also at the social and cultural one. The beginning of this battle is approached in this study